2020
DOI: 10.2196/21767
|View full text |Cite
|
Sign up to set email alerts
|

Smartphone and Mobile Health Apps for Tinnitus: Systematic Identification, Analysis, and Assessment

Abstract: Background Modern smartphones contain sophisticated high-end hardware features, offering high computational capabilities at extremely manageable costs and have undoubtedly become an integral part in users' daily life. Additionally, smartphones offer a well-established ecosystem that is easily discoverable and accessible via the marketplaces of differing mobile platforms, thus encouraging the development of many smartphone apps. Such apps are not exclusively used for entertainment purposes but are a… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
24
0
3

Year Published

2021
2021
2025
2025

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(27 citation statements)
references
References 55 publications
0
24
0
3
Order By: Relevance
“…It has already been suggested, that mobile applications offer a promising way for tinnitus assessment and treatment [76][77][78]. Hence, several speci c mobile applications will be developed for the UNITI-RCT creating the opportunity to signi cantly reduce the number of tinnitus-related clinical visits and as such the necessary health care resources.…”
Section: Discussionmentioning
confidence: 99%
“…It has already been suggested, that mobile applications offer a promising way for tinnitus assessment and treatment [76][77][78]. Hence, several speci c mobile applications will be developed for the UNITI-RCT creating the opportunity to signi cantly reduce the number of tinnitus-related clinical visits and as such the necessary health care resources.…”
Section: Discussionmentioning
confidence: 99%
“…16 Akıllı telefonlarda internet tabanlı uygulamalar ile tinnitus tedavisi yapılmasına yönelik çalışmalar yapılmıştır. 8,17 En sık kullanılan akıllı telefon uygulama platformlarında (iOS, Android) tinnitus ile ilgili olarak geliştirilmiş 200'e yakın uygulama bulunduğu ve bu uygulamaların, tinnitus hastalarının normal yaşamlarına katkı sağlayacak düzeyde iyileştirici etkilerinin olduğu öne sürülmüştür. 10 Bu uygulamalar, temelde ses tedavileri, bilgilendirme-eğitim, meditasyon-farkındalık, hipnoz, gevşeme egzersizleri, değerlendirme amacıyla kullanılmakla birlikte büyük bir çoğunluğu akustik maskeleme amacıyla kullanılmaktadır.…”
Section: Discussionunclassified
“…Previous research on tinnitus self-help interventions showed that the rate of dropout ranged from 0 to 66% [7]. Some very recent studies explored the use of eHealth tools among tinnitus patients (eg, [8][9][10]). A first attempt toward understanding the characteristics of users who discontinued using Tinnitus Talk was recently made in a master's thesis published by Hegde [11].…”
Section: Introductionmentioning
confidence: 99%
“…Intuitively, more negative perceptions of Tinnitus Talk could be associated with a higher probability of discontinuing use of the forum. Moreover, we were interested in potential associations between age and perceptions of Tinnitus Talk and reasons for discontinuing use, since older participants might have more problems with using the internet than younger participants [8,9]. Accordingly, our research questions were as follows: (1) What are the reasons for discontinuing the use of Tinnitus Talk?…”
Section: Introductionmentioning
confidence: 99%